Speak memory: an Oral History Centre in Braamfontein, Johannesburg - Scholes, Alexandra Alice (My University, 2016)
Sound, in the form of speech and song was celebrated in all preliterate societies. Oral history has recently come back into prominence, with the realisation that it can be more inclusive than traditional academic history and contribute to a shared experience within a group. In Post-Apartheid South Africa it played an important role in the TRC hearings. Organisations such as StoryCorps, have discovered the important therapeutic value gained by the sharing of stories between individuals and groups. The Speak Memory Oral History Centre aims to encourage historians to engage with oral history as a medium for memory recollection and to create a body of populist oral history testimonies. Oral history deals with memory and so the relationship between architecture and memory was investigated, with a particular focus on the neurological mechanisms involved in memory. An approach to the design of an Oral History Centre used these neurological mechanisms as design tools for a building that would facilitate the recording and recall of memory.
This document is submitted in partial fulfillment for the degree: Master of Architecture [Professional] At the University of the Witwatersrand, Johannesburg, South Africa, in the year 2016
Keywords: City planning--South Africa--Johannesburg; Architecture and history